COVID-19 and the Mission of the Church: Some Notes on the New Normal - Zandroto, Iman Jaya (International bulletin of mission research, 2021)
The COVID-19 pandemic has caused major changes in all areas of life, including the life of the church. It has caused the church to live in a new normal, challenging the church’s ability and perspective on how to carry out its mission. This article explores the mission of the church in the new normal. It provides consideration of health protocols, the use of technology, spirituality, and the church’s attitudes and actions toward the issues that are part of the new normal.